1984
DOI: 10.1021/bi00297a007
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of horse liver alcohol dehydrogenase by modification of cysteine residue 174 with 3-bromopropionic acid

Abstract: Horse liver alcohol dehydrogenase is inactivated with Michaelis kinetics at pH 7 and 25 degrees C by 3-bromopropionic acid. In the absence of NAD+, the Ki is 2 mM, and the pseudo bimolecular rate constant (k3/Ki) is 0.03 M-1 s-1; in the presence of 1 mM NAD+, Ki is 2.3 mM, and k3/Ki is 0.006 M-1 s-1. 3-Bromopropionic acid is a competitive inhibitor, Ki of 0.4 mM, against ethanol as a substrate. Inactivation was prevented in the ternary complexes with NAD+ X pyrazole and NADH X isobutyramide, was retarded by NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Hence, there is little effect of the substitution of the basic residues His in ß2 for Arg in ßi on iodoace tate binding at the active site of ADH. Exam ination of the specificity of inactivation of ßißi and ß2ß2 by iodoacetate indicates that a single Cys-174 is selectively and stoichiometrically alkylated [53], In a recent study, Chadha and Plapp [51] reported that Cys-174 of horse liver ADH is modified by the halo acid 3-bromopropionate. They pro posed that the carboxyl group of 3-bromopropionate interacts with the guanidino group of Arg-369 to form a MichaelisMenten complex which facilitates the alkyl ation of Cys-174.…”
Section: Inhibitors and Activators Of Human Liver Adh Isoenzymesmentioning
confidence: 99%
“…Hence, there is little effect of the substitution of the basic residues His in ß2 for Arg in ßi on iodoace tate binding at the active site of ADH. Exam ination of the specificity of inactivation of ßißi and ß2ß2 by iodoacetate indicates that a single Cys-174 is selectively and stoichiometrically alkylated [53], In a recent study, Chadha and Plapp [51] reported that Cys-174 of horse liver ADH is modified by the halo acid 3-bromopropionate. They pro posed that the carboxyl group of 3-bromopropionate interacts with the guanidino group of Arg-369 to form a MichaelisMenten complex which facilitates the alkyl ation of Cys-174.…”
Section: Inhibitors and Activators Of Human Liver Adh Isoenzymesmentioning
confidence: 99%
“…A variety of cysteine-alkylating reagents have been used to investigate the structure and catalysis mechanism of HLADH. Cys 46 and Cys 174, both zinc ligands in the active site in HLADH, are selectively alkylated by iodoacetate and 3-bromopropionate, respectively, with almost complete loss of activity (Harris, 1964;Li & Vallee, 1963;Chadha & Plapp, 1984). The mechanism of inactivation of HLADH by halo acids has been established by kinetic studies (Reynolds & McKinley-McKee, 1969;Dahl & McKinley-McKee, 1981a;Chadha & Plapp, 1984) and indicates that a high-affinity, reversible enzyme inhibitor Michaelis-Menten complex is formed prior to covalent modification.…”
mentioning
confidence: 99%
“…This finding agrees with reports on other ADHs, in which the cysteine ligand@) of the active site zinc were carboxymethylated in the native enzyme. Carboxymethylation of Cys 46 or Cys 174 of HLADH (Li & Vallee, 1963;Harris, 1964;Chadha & Plapp, 1984), Cys 43 of sorbitol dehydrogenase (Jeffery et al, 1981), and Cys 37 of TBADH (this study) abolished the catalytic activity of all three enzymes. In S. sulfaturicus, on the other hand, alkylating Cys 38 enhanced the catalytic activity of ADH (Raia et al, 1996).…”
Section: Discussionmentioning
confidence: 47%